Knowledge, attitudes, and willingness of patients with thyroid diseases toward thyroid thermal ablation techniques - Ying Liu; Lihong Liu; Jinling Wang; Jinke Li; Lu Zhou; Meng Wang; Weiwei Zhao; Liang Hao; Shurong Wang; Shoujun Yu (Scientific Reports)
Abstract To investigate the knowledge, attitudes, and willingness (KAW) of patients with thyroid disease regarding thyroid thermal ablation techniques and explore the factors associated with KAW. This cross-sectional survey was conducted at Yantai Hospital of Shandong Wendeng Orthopaedics & Traumatology and Yantai Affiliated Hospital of Binzhou Medical College between October 2022 and March 2023. This study included 632 patients; 66.14% were female. The mean knowledge, attitude, and willingness scores were 6.03 ± 2.42 (possible range: 0–10), 17.52 ± 2.91 (possible range: 5–25), and 33.02 ± 6.34 (possible range: 8–40), indicating poor knowledge, positive attitudes, and proactive willingness. Multivariable analysis showed that ≥ 51 years old, urban areas, consuming alcohol, medical treatment, and surgical treatment were independently associated with adequate knowledge. The knowledge scores, ≥ 51 years old, females, urban areas, medical treatment, and surgical treatment were independently associated with a positive attitude. Only the attitude scores were independently associated with proactive willingness. Patients with thyroid diseases have poor knowledge, positive attitudes, and proactive practice toward thermal ablation. Sustained efforts are required to increase knowledge about thyroid thermal ablation techniques.